Effect of Cover Crops, and the Management Thereof, on the Weed Spectrum in a Drip-irrigated Vineyard: 2. Weeds Growing From Grapevine Berry Set to Post-harvest - Fourie, J.C.; Kunjeku, E.C.; Booyse, M.; Kutama, T.G.; Freitag, K.; Ochse, C.H. (South African Journal of Enology and Viticulture, 2017)
A five-year trial (2009 to 2013) was executed in a drip-irrigated seven-year-old Shiraz/101-14 Mgt vineyard established on a sandy to sandy clay loam soil at Blaauwklippen Farm (33°58’S, 18°50’E) near Stellenbosch, South Africa. Fourteen treatments, consisting of two management practices applied to five cover crop species, as well as winter-growing weeds (no cover crop) and winter-growing weeds (no cover crop) with nematicide applied in the vine row, were applied. The weeds and cover crop species were eithercontrolled chemically (CC) or mechanically (MC) during grapevine bud break, followed by full-surface chemical control during berry set (for both CC and MC treatments). Rhynchelytrum repens (Natal redtop)dominated the post-harvest pre-treatment weed spectrum in all the treatments except Eruca sativa cv. Nemat (Nemat) (MC). This species lost its post-harvest dominance from 2010 onwards. It seems that the relatively low summer rainfall during the 2010/2011 season allowed Anagallis arvensis to appear in April 2011 and dominate some of the treatments, which coincided with the disappearance of Cynodon dactylon (common couch) and Polygonum aviculare (prostrate knotweed). Digitaria sanguinalis, common couch and prostrate knotweed seemed to establish better during late summer where MC was applied. The pre-treatment average post-harvest weed stand of 5.53 t/ha was reduced to 0.53 t/ha within one season, illustrating the benefit of full-surface chemical weed control applied during grapevine berry set.